The Mechanical Properties of Translucency Monolithic Zirconia vs Lithium Disilicate: A Systematic Review and Meta-analysis - Hamepaiboon, Phornnalat; Chukiatmun, Kannika; Posritong, Sumana (Journal of The Department of Medical Services, 2024)
Background: Patients’ demand for esthetic dentistry is increasing. Translucency monolithic zirconia is developed to be the material of choice in term of esthetics besides from lithium disilicate. Objective: To synthesize research findings and a meta-analysis on the mechanical properties of translucent zirconia monolithic versus lithium disilicate materials. Methods: Systematic searching for relevant research on the PubMed, open-access and Google Scholar, as well as conducting manual searches were done. Only articles in English or Thai from 2011 to 2021 were taken. The meta-analysis of ﬂexural strength, fracture resistance, and fracture toughness was performed from 11 accepted publications. Results: Translucency monolithic zirconia had a statistically significant higher ﬂexural strength than lithium disilicate, but the result was inconclusive due to the lack of data homogeneity (I2=97.8%). Translucency monolithic zirconia also shown statistically significant higher fracture toughness and fracture resistance than lithium disilicate, but the result was inconclusive due to the lack of homogeneity in the data (I2=96.3%, I2=86.9%) and insufficient studies. Conclusion: Translucent monolithic zirconia is the material of choice for esthetics in high biting forces area or patients with parafunctional habits, however; further high-quality studies are required.